2014
DOI: 10.1080/02640414.2014.969296
|View full text |Cite
|
Sign up to set email alerts
|

A six-year monitoring case study of a top-10 cycling Grand Tour finisher

Abstract: This study analysed the evolution of the physical potential of a twice top-10 Grand Tour cycling finisher (Tour de France and Vuelta a España) whose training was monitored between the ages of 18 and 23 years. The world-class cyclist's power output (PO) data and training indices were analysed over six years to determine the evolution of his record power profile and training load (TL), which were estimated by using the session rating of perceived exertion (RPE) method. The total annual duration and TL increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 32 publications
9
45
2
1
Order By: Relevance
“…Pinot and Grappe 11 reported very large correlations (r = 0.83 -0.94) between increases in training load quantified by sRPE and mean maximal power outputs (5 -240 min) achieved during training and competition each year. However, the study by Pinot and Grappe 11 was a case-study conducted over an extended period of time, and so it is hard to compare their results directly with ours.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pinot and Grappe 11 reported very large correlations (r = 0.83 -0.94) between increases in training load quantified by sRPE and mean maximal power outputs (5 -240 min) achieved during training and competition each year. However, the study by Pinot and Grappe 11 was a case-study conducted over an extended period of time, and so it is hard to compare their results directly with ours.…”
Section: Discussionmentioning
confidence: 98%
“…This has previously been shown in a study by Manzi et al 6 with eight recreational long-distance runners. These authors reported that speed at 2 mmol·L Even though internal training load methods such as bTRIMP 10 , Lucia's TRIMP (luTRIMP) 5 and session-RPE (sRPE) 11 and external training load methods such as Training Stress Score™ (TSS) 12 are mentioned in the literature, there is little evidence of a doseresponse relationship between these measures and training outcomes. Other measures of training load such as Edwards' TRIMP (eTRIMP) and iTRIMP have been applied in other sports but not in cycling.…”
Section: Introductionmentioning
confidence: 99%
“…36 PPO is a parameter that indicates the aerobic potential of cyclists. 37 In HRV-G, PPO increased significantly and presented possible beneficial effects. Furthermore, HRV-G presents a greater magnitude of change than TRAD (Table 3).…”
Section: Regarding These Differences Training Prescription Based On mentioning
confidence: 95%
“…The external workload in professional male cyclists has been previously described during road racing [2][3][4][5][6] and training. 7 While these studies add to a wealth of knowledge on external workload, the within-season distribution of workload during both training and racing is not well understood.…”
mentioning
confidence: 99%